Educational intervention on teenage pregnancy in the Nuevitas municipality, Camagüey, 2020-2021 - Norki Betancourt Sánchez; Leydis Suárez Ramos; Yusnai Vázquez Cervantes; Moraima Martell Martínez (Medisur)
Background: the beginning of sexual activity exposes adolescents to a series of risks that compromise their sexual and reproductive health, as well as their psychological and social development. Objective: to describe the application and results of an educational intervention on pregnancy in adolescence. Methods: an educational intervention study was carried out in adolescents from 12 to 18 years of age (N=107), belonging to the health area of the Francisco Peña Peña Polyclinic, Nuevitas municipality, Camagüey, from 2020 to 2021. The research was organized in three stages: diagnosis, intervention and evaluation. The studied variables were about the knowledge about the right age to start sexual relations; optimal age for pregnancy; contraceptive methods; and maternal and child complications of pregnancy in adolescence. Results: the intervention was able to raise knowledge about the appropriate age for the start of sexual intercourse, which ranged from 34.6% to 96.3%. About the optimal age to carry a pregnancy, 90.6% of adolescents were better oriented after applying the strategy. Once the study was completed, the level of knowledge in general rose to 85%. Conclusion: The educational intervention was effective in increasing knowledge about pregnancy in adolescence, and about the maternal and child complications that it entails in this stage of life.